Accumulation mechanism of Cd and Pb in raddish roots - CHEN Ying-xu; LIN Qi; LU Fang; JIN Guo-xian (浙江大学学报. 农业与生命科学版, 2000)
The accumulation mechanism of Cd and Pb in raddish roots was studied. The results showed that in the first 12 hours the accumulation process of Pb in roots was probably due to rapid adsorption, later, to slow chemical precipitation and cell absorption. Especially, at high Pb content, chemical precipitation played a progressively more important role in Pb removal. The accumulation of Cd in roots was mainly due to adsorption in the first 24 hours, later, absorption process maybe was dominant. In Pb-Cd treatment, the competitive adsorption and antagonistic absorption of Pb and Cd in roots had certain effect on the accumulation mechanism of Pb or Cd.